2013
DOI: 10.1177/0269758013492753
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of risk

Abstract: This review consolidates the research on perceptions of risk and its antecedents to improve our understanding of the factors that influence perceptions of risk. The evidence is evaluated against the available models, theories and explanations. Online databases, relevant journals and books were searched using keywords resulting in a total of 30 papers being included in this review. It was found that the literature provided support for previous victimization, experienced both directly and vicariously, gender, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…These findings suggest that participants who think they live in areas with lower crime rates where they feel safe are found to express more positive attitudes towards the police than do those who live in areas where there are higher crime rates where they do not feel safe (Cheng, 2015;Hwang, McGarrell, & Benson, 2005;Skogan, 2005). Areas with perceived low crime rates are associated with greater collective efficacy, where participants have a greater social cohesion and level of interaction with their neighbours, which is consistent with the findings of previous research (Hicks & Brown, 2013). We found that those who feel they live in ethnically diverse neighbourhoods see more Signs of Social and Physical Disorder and have lower Collective Efficacy and Trust in Police.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These findings suggest that participants who think they live in areas with lower crime rates where they feel safe are found to express more positive attitudes towards the police than do those who live in areas where there are higher crime rates where they do not feel safe (Cheng, 2015;Hwang, McGarrell, & Benson, 2005;Skogan, 2005). Areas with perceived low crime rates are associated with greater collective efficacy, where participants have a greater social cohesion and level of interaction with their neighbours, which is consistent with the findings of previous research (Hicks & Brown, 2013). We found that those who feel they live in ethnically diverse neighbourhoods see more Signs of Social and Physical Disorder and have lower Collective Efficacy and Trust in Police.…”
Section: Discussionsupporting
confidence: 89%
“…Research examining crime-related risk has ranged from the perception of how safe it is being alone at night, the perceived likelihood of becoming a victim in general or of specified individual offences, or perceptions of an increase of crime, to a perceived neighbourhood criminality (Hicks & Brown, 2013). It is increasingly accepted that measuring perceived risk requires a careful definition of who is perceived to be at risk (i.e.…”
Section: Perceived Risk Of Victimisationmentioning
confidence: 99%
See 2 more Smart Citations
“…One closing methodological issue is the inequality in the gender distribution, with women accounting for approximately 78 percent of the sample. With prior research suggesting gender differences in some areas of risk perception, we might get different results with a more equally distributed sample (Hicks and Brown, 2013). However, there are no clear arguments for assuming that gender moderates either the relationship between EFT and perceived risk or the interaction between EFT and imaginability.…”
Section: Additional Methodological Considerationsmentioning
confidence: 67%